Exposure to blue light reduces antimicrobial resistant Pseudomonas aeruginosa isolated from dog ear infections - Gigante, Adriano M.; Hadis, Mohammad A.; Secker, Bailey; Shaw, Stephen C.; Cooper, Paul R.; Palin, William M.; Milward, Michael R.; Atterbury, Robert J. (Frontiers in Microbiology, 2024)
Introduction Pseudomonas aeruginosa is a leading cause of canine otitis externa. Enrofloxacin is often applied topically to treat this condition, although recalcitrant and recurring infections are common. There is evidence that exposure to blue light (400–470 nm) has a bactericidal effect on P. aeruginosa and other microorganisms. Methods In the present study, we tested the biocidal effect of blue light (375–450 nm), alone or in combination with enrofloxacin, against six isolates of P. aeruginosa from dogs with otitis externa (5 of which were resistant to enrofloxacin). Results Treatment of planktonic cell cultures with blue light resulted in significant (p < 0.5) reductions in Colony Forming Units (CFU) for all seven strains tested, in some cases below the limit of detection. The greatest bactericidal effect was observed following exposure to light at 405 nm wavelength (p < 0.05). Exposure to blue light for 20 min usually resulted in a greater reduction in Pseudomonas aeruginosa than enrofloxacin treatment, and combination treatment typically resulted in the largest reductions in CFU. Analysis of the genome sequences of these strains established that enrofloxacin resistance was likely the result of a S466F substitution in GyrB. However, there was no clear association between genotype and susceptibility to blue light treatment. Discussion These results suggest that blue light treatment, particularly at 405 nm wavelength, and especially in combination with enrofloxacin therapy, could be an effective treatment for otherwise recalcitrant canine otitis externa caused by Pseudomonas aeruginosa. It may also provide a way of extending the usefulness of enrofloxacin therapy which would otherwise be ineffective as a sole therapeutic agent.